The relationship between seven anaerobic tests and swim performance - Rohrs, D. M.; Mayhew, J. L.; Arabas, M. S.; Shelton, M. (Journal of Swimming Research, 1990)
7 tests of anaerobic power and capacity were related to performance in a heterogeneous group of college male and a homogeneous group of female swimmers. Implications: The anaerobic testing of a homogeneous group (e.g., a national team) will not yield valuable scientific information. All that can be determined is scores for the tests. Within the group, if one athlete scores better than another, that does not mean anything of significance about swimming performance. It is incorrect to compare swimmers on results from tests like these when the swimmers all perform at the same standard. The only value would be to compare each swimmer's past scores on tests, if changing test scores is important. It should be remembered that alterations in test results are not related to alterations in swimming performance in high-standard swimmers. There may be some value in using anaerobic tests for talent identification. The swim bench test might be a good preliminary test to locate non-swimmers who have high anaerobic power and capacity. However, it should be remembered that these tests only partially reflect what is involved in swimming and that they should be used in conjunction with other screening devices. If any anaerobic testing is to be done with higher calibre swimmers, it should be done in the water, an activity that is more swimming specific than those done on land.